ANALISIS KEMAMPUAN KEUANGAN DAERAH PEMERINTAH KABUPATEN JAYAPURA - La Ode Abdul Wahab; Siti Rofingatun; Balthazar Kreuta (Universitas Cenderawasih, 2017)
The purpose of this paper is to analyze and obtain empirical evidence about the financial performance of Jayapura regency government in fiscal year 2010-2014, measured from the level of independence of local, regional dependency rate, the level of fiscal decentralization, the level of effectiveness and efficiency of financial management and fiscal capacity Jayapura regency in fiscal year 2010-2014, measured through share and growth Local Revenue. The results obtained from this study is that the financial capacity of Jayapura regency, measured from the level of the region's autonomy in fiscal year 2010-2014 included in the criteria are lacking, and the level of dependence of the region in that period qualifies as a very high criteria instructive relationship patterns. The ratio of fiscal decentralization is still lacking, the level of effectiveness of regional revenue in 2010-2014 classified in the category of very effective with a ratio of regional revenue collection efficiency is very efficient. The financial capacity of the district of Jayapura in this case the level of independence and dependence of the area and the level of fiscal decentralization is considered good if the government of Jayapura District has been able to raise the percentage of acceptance of regional revenue to be in the top 40% of the fund balance, because then the Local Revenue will contribute greater of the total regional expenditure. Keywords: financial capacity of local, regional autonomy, regional dependence, fiscal decentralization, effectiveness, efficiency